Implementasi Metode First Expired First Out (FEFO) pada Sistem Manajemen Inventaris Distributor Daging Berbasis Web - Laely Syafitri; Susanto Susanto; Titis Handayani (Jurnal Teknologi Informasi dan Multimedia, 2026)
Frozen meat inventory management by distributors requires the implementation of a system that can maintain product quality while reducing the risk of losses due to expired meat. CV. Heimon Anugrah Pangan still experiences several obstacles in manual stock recording which causes data synchronization and accumulation of old products in the warehouse. This study aims to imple-ment FEFO based on expiration dates in a web-based inventory management system. The system development technique used in this study is the waterfall method with steps starting from needs analysis, system design, implementation, testing, and maintenance. The system was created using PHP and MYSQL with in-bound and outbound management features, notification of stock ap-proaching expiration, and automatic reports in PDF format. As a result, the FEFO method can be implemented by the system with product expenditure priorities based on batches and the nearest expiration date. In system trials with black box testing, all features were proven to work accord-ing to user expectations. With this system, inventory management can be carried out effectively, efficiently, and with minimal human error.